Penyuluhan Pembuatan Kerajinan Bunga Akrilik Pada Anak Desa Jawa Tonga II untuk Membangun Karakter Entrepreneurship - Maryanto Saragih; Herna Febrianty Sianipar (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2021)
The economy of the people of Jawa Tonga II Village is classified as low because in general parents work as farmers, this has an impact on the children's lack of enthusiasm in achieving their goals. Many of them think that earning income has to work for other parties. The children also do not understand the knowledge of entrepreneurship. This program aims to build entrepreneurial character in the children of Jawa Tonga II Village and have creative hands-on skills activities. Not all elementary schools are able to provide teaching arts including handicrafts optimally, this can be seen from the factor of educators who are less enthusiastic about teaching art so that children are less able to unleash their creativity and skills in creating arts. Teaching arts, especially handicrafts, is very much needed by elementary school level children for the development of their creativity, with the handicraft arts training conducted by students of the HKBP Nommensen Pematangsiantar University can make children skilled, active, and able to show their creativity and understand the use of goods around them. Students together make work with direction from the teacher and according to the examples that have been prepared previously. The method of implementing activities includes three stages, namely: planning, action and evaluation. The results of program implementation are (a) there is an increase in children's creativity and skills in good categories, (b) good quality acrylic flower handicrafts.